(untitled) (Maco’ou : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to enhance the knowledge and skills of goat farmers in Dusun Bangko regarding the production of silage from elephant grass. The training was conducted over two days and attended by 30 farmers. The methods employed included presentations, discussions, and hands-on practice. Evaluation results showed a significant increase in participants’ knowledge and skills, with an average improvement of 40% based on pre-test and post-test assessments. This program positively impacts the understanding of feed processing, which is expected to improve productivity and the welfare of farmers. It is hoped that this activity will be followed by ongoing assistance and broader socialization regarding the benefits of silage to enhance feed quality within the community.